Heat transfer in aerospace applications - Sundén, Bengt; Fu, Juan (Amsterdam Academic Press, 2017)
Heat Transfer in Aerospace Applications is the first book to provide an overall description of various heat transfer issues of relevance for aerospace applications. The book contains chapters relating to convection cooling, heat pipes, ablation, heat transfer at high velocity, low pressure and microgravity, aircraft heat exchangers, fuel cells, and cryogenic cooling systems.

Chapters specific to low density heat transfer (4) and microgravity heat transfer (9) are newer subjects which have not been previously covered. The book takes a basic engineering approach by including correlations and examples that an engineer needs during the initial phases of vehicle design or to quickly analyze and solve a specific problem. Designed for mechanical, chemical, and aerospace engineers in research institutes, companies, and consulting firms, this book is an invaluable resource for the latest on aerospace heat transfer engineering and research.--Provided by publisher.
Chapter 1 : Introduction -- Chapter 2 : Ablation -- Chapter 3 : Aerodynamic Heating: Heat Transfer at High Speeds -- Chapter 4 : Low-Density Heat Transfer: Rarefied Gas Heat Transfer -- Chapter 5 : Cryogenics -- Chapter 6 : Aerospace Heat Exchangers -- Chapter 7 : Heat Pipes for Aerospace Application -- Chapter 8 : Fuel Cells -- Chapter 9 : Microgravity Heat Transfer -- Chapter 10 : Computational Methods for the Investigations of Heat Transfer Phenomena in Aerospace Applications -- Chapter 11 : Measuring Techniques -- Appendix 1 : Governing Equations for Momentum, Mass, and Energy Transport -- Appendix 2 : Dimensionless Numbers of Relevance in Aerospace Heat Transfer -- Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Heat -- Transmission; Electronic books